1984
DOI: 10.1177/00220345840630050401
|View full text |Cite
|
Sign up to set email alerts
|

Single Bovine Enamel Particles Examined by Electron Optics

Abstract: Whole enamel scrapings from teeth of embryonic calves have been separated by density gradient centrifugation in organic solvents into fractions (1.6 less than p less than 2.4 g/cm3) representing progressive stages of mineral phase maturation. Single enamel particles or their small aggregates from such fractions were examined by transmission electron microscopy, electron diffraction, and high-spatial-resolution electron probe micro-analysis. The electron optical methods demonstrated the presence of poorly cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, subsequent studies could find no evidence of octacalcium phosphate in embryonic bovine enamel (Landis and Navarro ; Landis et al. , ). The initial mineral in enamel is currently believed to be a transient amorphous calcium phosphate (ACP) phase that converts into HAP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, subsequent studies could find no evidence of octacalcium phosphate in embryonic bovine enamel (Landis and Navarro ; Landis et al. , ). The initial mineral in enamel is currently believed to be a transient amorphous calcium phosphate (ACP) phase that converts into HAP.…”
Section: Discussionmentioning
confidence: 97%
“…Long ago it was proposed that the initial mineral phase in enamel is octacalcium phosphate (Brown 1965;Simmer and Fincham 1995). However, subsequent studies could find no evidence of octacalcium phosphate in embryonic bovine enamel (Landis and Navarro 1983;Landis et al 1984Landis et al , 1988. The initial mineral in enamel is currently believed to be a transient amorphous calcium phosphate (ACP) phase that converts into HAP.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding carbonate influence on CalP, in samples of enamel particles separated according to increasing density, Landis et al (1984) found a correlative Ca/P ratio except in the lowest density fractions which they suggested may have a higher calcium carbonate content. A similar effect on Ca/P may also occur if the opossum tooth germ contained the same carbonate species.…”
Section: Composition and Distribution Of Intrinsic Elementsmentioning
confidence: 90%
“…Interrod progressively analyzed -1.2-1.3 (Landis and Glimcher, 1978)], a n octacalcium phosphate standard [CaR -1.34 (Landis and Glimcher, 1978)], and a calcium phosphate containing poorly crystalline hydroxyapatite [CaJP = 1.45 (Roufosse et al, 1979). Most of the rat enamel CaJP ratios are lower than density fractions of embryonic bovine enamel [ C d P = 1.48-1.82 (Landis and Navarro, 1983;Landis et al, 1984)l and a well-crystallized synthetic hydroxyapatite [ C a = 1.62 (Roufosse et al, 197911. In terms of electron diffraction, the reflections of initial and inner enamel are characteristic of those of a very poorly crystalline hydroxyapatite. Similar electron diffraction patterns have also been identified under comparable conditions in all embryonic bovine enamel density fractions (Landis et al, 1984), intermediate and higher-density fractions of embryonic chick bone (Roufosse et al, 1979), whole unfractionated embryonic and postnatal (14 week) chicken bone (Roufosse et al, 19791, and thin tissue sections of early extracellular mineral deposits in rat growth plate cartilage (Landis and Glimcher, 1982) and embryonic chick tibiae (Landis and Glimcher, 1978).…”
Section: )mentioning
confidence: 99%